Untersuchung des Sinterverhaltens von SrTiO? unter Berücksichtigung der Defektchemie - Lemke, Fabian (KIT Scientific Publishing, 2016)
Space charge contributions to the densification of perovskite ceramics during sintering were assessed in the model system strontium titanate using a combined experimental and analytical approach. Defect chemistry in the bulk and at the grain-boundaries for SrTiO? in high temperature regions were calculated based on literature data. Diffusion coefficients for bulk-diffusion and grain boundary-diffusion were estimated and used with Coble s equations for densification rates.
German
Keywords: Sintern; microstructure; SrTiO?; Defektchemie; sintering; Strontiumtitanat; Mikrostrukturstrontiumtitanat; defect chemistry